2005
DOI: 10.1166/jnn.2005.219
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Fe<SUB>2</SUB>O<SUB>3</SUB> Nanoparticles Combined with Magnetic Fluid Hyperthermia on Cultured Liver Cancer Cells and Xenograft Liver Cancers

Abstract: The therapeutic effect of Fe2O3 nanoparticles combined with magnetic fluid hyperthermia (MFH) on human hepatocarcinoma SMMC-7721 cells in vitro and xenograft liver cancer in nude mice is studied. We examined growth and apoptosis of SMMC-7721 cells treated with MFH containing Fe2O3 nanoparticles at various concentrations (2, 4, 6, and 8 g/liter) for 30-60 min by using MTT, flow cytometry (FCM), and transmission electron microscopy (TEM). We also observed weight and volume inhibitory rates of the tumors of SMMC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Yan et al showed that treatment using Fe 2 O 3 nanoparticles combined with magnetic field hyperthermia could inhibit not only the proliferation of cultured liver cancer cells, but also induce apoptosis of cultured liver cancer cells. Moreover, they showed that this hyperthermic strategy has a significant inhibitory effect on the weight and volume of xenograft liver cancer [25]. Similarly, Hilger et al [26] showed the feasibility of thermal ablation of breast cancer with magnetic nanoparticles using an animal model.…”
Section: Novel Hyperthermia Induced Using Magnetic Materialsmentioning
confidence: 96%
“…Yan et al showed that treatment using Fe 2 O 3 nanoparticles combined with magnetic field hyperthermia could inhibit not only the proliferation of cultured liver cancer cells, but also induce apoptosis of cultured liver cancer cells. Moreover, they showed that this hyperthermic strategy has a significant inhibitory effect on the weight and volume of xenograft liver cancer [25]. Similarly, Hilger et al [26] showed the feasibility of thermal ablation of breast cancer with magnetic nanoparticles using an animal model.…”
Section: Novel Hyperthermia Induced Using Magnetic Materialsmentioning
confidence: 96%
“…The results of electron microscopy, X-ray spectroscopy and calorimetric measurements in several studies have confirmed that the use of magnetic fluids with strengths between 4-12.5 kA m -1 and frequencies in the region 500-800 kHz (depending on the used magnetic nanoparticles) is optimal for producing heating of magnetic fluids up to 42°C, which is required for successful MFH treatments (83)(84)(85)(86).…”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 82%
“…In several studies, the application of Fe 2 O 3 nanoparticles in MFH treatments has been investigated in vivo on patients with hepatocellular carcinoma (86,87). The use of iron oxide particles inhibits proliferation and induces apoptosis of SMMC-7731 tumor cells and thus has a significant inhibitory effect on the mass and volume of treated cancer, superior to the effects produced by conventional anticancer therapies.…”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 99%
“…9,10 Furthermore, the nanoparticles can be used to deliver anticancer drugs and reversal agents to improve the efficiency of treatment as well as to overcome drug resistance. 11,12 Nowadays, some Chinese herbal medicines are considered to be able to reverse multidrug resistance in the treatment of cancer. 5 Previous research has demonstrated that 5-bromotetrandrine (5-BrTet) can partly inhibit the function of P-glycoprotein, suppress antiapoptosis, and accumulate anticancer drugs in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%